BEBERAPA HIPOTESIS TENTANG EKSKLUSI SOSIAL DI INDONESIA - Robert M.Z. Lawang (Jurnal Ilmu Sosial Mamangan, 2014)
Although the concept of social exclusion was developed in Western society context, the same phenomenon has been part of Indonesian societies today in somewhat different nature. It is true that social exclusion is related to both issues of poverty and underclass position as well, but approach to solve the problem has been starting from point related to one of them as accentuation. Regardless of performance achieved, Government of Indonesia has been considering the issues in the programs of concerned ministries.